Innovaciones en la educación peruana - Campos Arenas, Agustín (2015)
This article focuses on the innovations thathave taken place in peruvian education. Theauthor presents four attempts to innovateeducation in the country. One that affectedthe entire education system (educationalreform). Another, focuses in the pedagogicaland didactic action in schools (DCN) andfinally two proposals: high school anddistance education.